Pengaruh Gaya Kepemimpinan, Budaya Organisasi dan Kompensasi Finansial terhadap Kepuasan Kerja Karyawan pada PT. Dunia Garmen Internasional di Denpasar - Mega Rosa Arini Putri, Anak Agung (E-Jurnal Manajemen, 2014)
Normal 0 false false false EN-US ZH-CN X-NONE MicrosoftInternetExplorer4 Job satisfaction is an emotional attitude with a sense of fun and love for his job . This attitude can be seen on the morale , discipline and the ability to work . The purpose of this study is to determine what influences leadership style , organizational culture and financial compensation to employee satisfaction and simultaneously also partial to see the dominant variables that influence employee job satisfaction . Data analysis techniques used in testing the hypothesis that the factor analysis and multiple linear regression analysis . The results of these discussions to produce data that leadership style , organizational culture and financial compensation has a significant influence on job satisfaction simultaneously employees at PT . Denpasar International Garments world with a contribution of 19.8 percent . /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:SimSun; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}